The initial boundary value problem of a mixed-typed hemivariational inequality - Guo Xingming (International Journal of Mathematics and Mathematical Sciences)
A mixed-typed differential inclusion with a weakly continuous nonlinear term and a nonmonotone discontinuous nonlinear multi-valued term is studied, and the existence and decay of solutions are established.